Inhibitory Effect of Ejiao Jelly Extract on Hyaluronidase Activity and Its Influence on Lipid Synthesis in SZ95 Cells - MENG Ling-feng; LI Cong; WEI Zi-cheng; MA Xue-ying; ZHANG Jian-ling; YUAN Yu-jiao; YU Qun; FAN Liu-ping (Liang you shipin ke-ji)
Ejiao jelly’s main ingredients include donkey-hide gelatin, walnuts, and black sesame seeds, which are rich in active components and possess certain antioxidant properties. This study employed four different extraction methods to obtain active substances from commercial Ejiao jelly. Based on the analysis of active components, in vitro hyaluronic acid inhibition tests, and SZ95 cell experiments, we explored the skincare effects of Ejiao jelly. The results showed that Ejiao jelly could significantly inhibit hyaluronidase activity, with the alcoholic extract of Ejiao jelly demonstrating the best inhibitory effect, reaching an inhibition rate of 64.58%1.80%. The cytotoxicity of Ejiao jelly extracts on SZ95 cells was tested using the CCK-8 method, revealing no cytotoxicity within the concentration range of 25-400 g/mL. The inhibitory effect of Ejiao jelly extracts on lipid synthesis in SZ95 cells was concentration-dependent. The alcoholic extract of Ejiao jelly at 400 g/mL showed the strongest effect in reducing lipid content in SZ95 cells, with an inhibition rate of 47.90%4.88%. This research provides a theoretical basis for investigating the skincare benefits of Ejiao jelly and has practical application value.